The Effects of the MFA Phase Out on the Philippine Garments and Textiles Industries - Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 1996)
Over the years, Multi-Fibre Agreement has assured the Philippines markets for its exportable textiles and garments. Given that the Multi-Fibre Agreement will be abolished by January 2005, issues have been raised regarding the sector's competitiveness, since phasing out MFA indicates opening up the global market to the best and most efficient product suppliers. This paper analyzes the survival of the Philippine textiles and garment industries considering its threatened comparative advantage even during the MFA years. In particular, this paper analyzes the sector's export performance concentrating on the role and administration of quota in the Philippines.
Keywords: 330; Multi-Fibre Agreement; garments and textile industries; quota utilization rates; export quota allocation